Effects of particle size on the triboelectrification phenomenon in pharmaceutical excipients: Experiments and multi-scale modeling - Raj Mukherjee; Vipul Gupta; Shivangi Naik; Saurabh Sarkar; Vinit Sharma; Prasad Peri; Bodhisattwa Chaudhuri (Elsevier, 2016)
Particle sizes play a major role to mediate charge transfer, both between identical and different material surfaces. The study probes into the probable mechanism that actuates opposite polarities between two different size fractions of the same material by analyzing the charge transfer patterns of two different sizes of microcrystalline cellulose (MCC). Quantum scale calculations confirmed alteration of charge transfer capacities due to variation of moisture content predicted by multiple surface and bulk analytical techniques. Discrete Element Method (DEM) based multi-scale computational models pertinent to predict charge transfer capacities were further implemented, and the results were in accordance to the experimental charge profiles.